2017
DOI: 10.1096/fj.201700283r
|View full text |Cite
|
Sign up to set email alerts
|

TRAP1 ameliorates renal tubulointerstitial fibrosis in mice with unilateral ureteral obstruction by protecting renal tubular epithelial cell mitochondria

Abstract: Mitochondrial dysfunction causes renal tubular epithelial cell injury and promotes cell apoptosis and renal tubulointerstitial fibrosis (TIF) progression. TNF receptor-associated protein 1 (TRAP1) is a molecular chaperone protein that is localized in mitochondria. It plays an important role in cell apoptosis; however, its functional mechanism in TIF remains unclear. In this study, we observed the effects of TRAP1 in renal tubular epithelial cell mitochondria in mice with unilateral ureteral obstruction and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Recent studies prove the potential renoprotective role of several intrinsic modulation factors that are closely related to mitochondrial function. Either downregulation of dynamin-related protein 1 17 or upregulation of NAD-dependent deacetylase sirtuin-3, mitochondrial 18 or TNF receptor associated protein 1 19 could have a protective effect on mitochondrial function in TECs and ameliorate renal fibrosis.Please spell out DRP117, SIRT318 and TRAP1in text, as it is mentioned only once.DRP1 stands for dynamin-related protein 1SIRT3 stands for NAD-dependent deacetylase sirtuin-3, mitochondrialTRAP1 stands for TNF receptor associated protein 1 (TRAP1)…”
Section: What Are the Intracellular Changes Of Tecs Upon Injury?mentioning
confidence: 99%
“…Recent studies prove the potential renoprotective role of several intrinsic modulation factors that are closely related to mitochondrial function. Either downregulation of dynamin-related protein 1 17 or upregulation of NAD-dependent deacetylase sirtuin-3, mitochondrial 18 or TNF receptor associated protein 1 19 could have a protective effect on mitochondrial function in TECs and ameliorate renal fibrosis.Please spell out DRP117, SIRT318 and TRAP1in text, as it is mentioned only once.DRP1 stands for dynamin-related protein 1SIRT3 stands for NAD-dependent deacetylase sirtuin-3, mitochondrialTRAP1 stands for TNF receptor associated protein 1 (TRAP1)…”
Section: What Are the Intracellular Changes Of Tecs Upon Injury?mentioning
confidence: 99%
“…TRAP1, a mitochondrial molecular chaperone, has been confirmed to have complex and numerous functions [26,27]. It has also been proven to play important roles in tubular epithelial cell mitochondrial injury induced by unilateral ureteral obstruction [28]. However, whether TRAP1 is involved in the regulation of renal tubule damage in DKD remains undefined.…”
mentioning
confidence: 99%
“…It was reported that melatonin prevented mitochondrial edema, cristae dilatation and maintained the integrity of mitochondrial membrane, thereby alleviating renal fibrosis 8 . TNF receptor-associated protein 1 (TRAP1) could inhibit the fibrosis-related proteins expression in renal tubular epithelial cells (TECs) and tubulointerstitial fibrosis by alleviating mitochondrial vacuolation, swelling, matrix density reduction and mitochondrial cristae rupture, and increasing the number of mtDNA copies 81 .…”
Section: Mitochondrial Dysfunction In Renal Fibrosismentioning
confidence: 99%
“…Maintaining the integrity of mitochondrial morphology and structure; 2. Increasing the number of mtDNA copies 81 Renal Bendavia Reducing oxidative damage of mitochondrial cardiolipin 83 , 84 Renal/renal ischemia reperfusion injury Postconditioning therapy Protecting mitochondria from oxidative stress-induced mtDNA damage 85 Renal 1,25-dihydroxyvitamin D3 Maintaining the ATP synthase activity 87 Renal Deletion of NLRP3 Alleviating oxidative stress and ROS production 88 91 Renal Combined treatment of MSC and melatonin 1. Melatonin enhanced the role of MSC in fibrosis treatment; 2.…”
Section: Therapeutic Strategies Targeting Mitochondria To Alleviate Fmentioning
confidence: 99%